2001
DOI: 10.1007/s003300000467
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal thoracoabdominal tumor mimicking pulmonary sequestration: a diagnosis dilemma

Abstract: Thoracoabdominal masses are among the many congenital anomalies being detected in fetus. The differential diagnosis of such anomalies include cystic adenomatoid malformation, pulmonary sequestration, neuroblastoma, lymphangioma, congenital diaphragmatic hernia, and bronchial atresia. We report a fetal thoracoabdominal mass that proved to be an angioma that was treated by partial embolization. Complete regression was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Detection of a systemic artery from the aorta to the fetal lung mass by 2D color power Doppler sonography is a key feature for the diagnosis of fetal pulmonary sequestration, but this is not 100% sensitive5. Distinguishing pulmonary sequestration from Type III congenital cystic adenomatoid malformation (CCAM) would be of interest in order to inform the parents and to plan the postnatal management6–9.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of a systemic artery from the aorta to the fetal lung mass by 2D color power Doppler sonography is a key feature for the diagnosis of fetal pulmonary sequestration, but this is not 100% sensitive5. Distinguishing pulmonary sequestration from Type III congenital cystic adenomatoid malformation (CCAM) would be of interest in order to inform the parents and to plan the postnatal management6–9.…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal manifestations of the congenital diaphragmatic hemangioma include polyhydramnios, hydrothorax, and cardiac shift. 22 This case demonstrated that with prenatal ultrasound confirming unilateral pleural effusion, MRI should be considered to exclude fetal congenital diaphragmatic hemangiomas. Fetal ultrasound or MRI can show high echogenic masses in the chest.…”
Section: Vascular Diseasesmentioning
confidence: 80%
“…Fetal ultrasound or MRI can show high echogenic masses in the chest. 22,23 Lymphatic Vessel Diseases 1. Primary lymphatic vessel abnormalities: CPL causes chylothorax and systemic lymphatic dilatation syndrome.…”
Section: Vascular Diseasesmentioning
confidence: 99%
“…Rapidly involuting congenital hemangiomas, including multifocal and visceral hemangiomas, may take weeks to months to involute, favoring a concerted, patient effort at nonoperative management in newborns whose symptoms from the hemangioma are clinically favorable [11]. A previous congenital thoracoabdominal angioma showed signs of significant spontaneous regression by 6 months, at which time it was amenable to embolization [12]. The use of steroids to promote involution in a neonate is not without potential morbidity with regard to long-term developmental effects.…”
Section: Discussionmentioning
confidence: 97%